Video-Conferencing for Outreach Communication Strategy to Enhance Academic Publishing and Research Communication in Africa - Okoka, Wilson; Nagasha, Irene Judith (My University, 2016)
The paper presents the effectiveness of video-conferencing community outreach projects in enhancing research ethics communication for public awareness in Uganda. It sets out to establish how vital the practice of research ethics in cross-cultural environment was in enhancing the smooth tripartite interactions among the researchers, communities and host institutions. The objectives were to: get an overview of community outreach research ethical issues and communication strategies; establish researchers’ outreach methods (approaches); identify the ethical challenges facing inter-cultural research in the country; assess the key enablers of community research ethics; and discover creative methods of infusing ethics in a cross-cultural community research. This review was conducted by sourcing documents, current literature and news bulletins, online search engines, through discussion with key informants, documents from Ugandan government specifically the ministries or national as well as international bodies, and lessons learned from research ethical practice. The findings were generally disappointing, contrary to the widely issued guidelines. There are rampant unresolved ethical issues that are worsened by communication gaps; field ethical challenges include: wrong attitudes, behaviour, methodology, perceptions, communication strategies, and cultural illiteracy; commonalities of outreach themes, agreements, modalities, methods, target communities, networks, and funding sources; many absentee field researchers and fictitious research sites; and weak ethics culture. Ethical issues are prompted by flouting guidelines, weak or lack of capacity, experience, integrity, professionalism, communication skills, or ignorance. There are multiple gaps in university coordination, concepts, methods, planning, budgeting, and implementation leading to project failures, budget overruns, conflicts, and disincentives. Community participation ensures trust, effective communication, and social acceptance. Inter-cultural community involvement promotes ethical research good practice among the researchers themselves on one hand, and the inter-cultural demographics plus the host institutions, on the other. Outreaches are critical for achieving early adoption and widespread diffusion of research ethics and culture in communities. They should be well planned, implemented, monitored, and evaluated for enhanced participation, transparency, empowerment, mutual trust, sustainability, and gender equality to achieve SDGs in Uganda.
Keywords: Video-conferencing; Communication Strategy; Academic Publishing; Research Communication; Africa; Gender Equality